Proton-Mr-Spectroscopy of the Breast: is it A Reliable Imaging Modality for Characterizing the Bi-Rads 3 And 4 Lesions Before the Biopsy? - Ayd?n, Hasan; Öztürk, Emine; K?z?lgöz, Volkan; Güzel, Hakan; Hekimo?lu, Baki (JOURNAL OF ADVANCES IN BIOLOGY, 2019)
Aim; Our aim is to evaluate the diagnostic performance of pre and post contrast proton MR spectroscopy (H-MRS) in patients with breast imaging-reporting data system (BI-RADS) 3 and 4 lesions. Materials and Methods; After institutional review board approval and informed consent taken from all the patients; breast MR imaging and unenhanced-enhanced spectroscopy was performed in 55 patients with BI-RADS 3 and 4 lesions. We had 4 DCIS, 5 malignant tumours, 1 borderline phylloides tumour, 3 mastititis and 42 benign masses in both groups. Diagnostic interpretation was based on the BI-RADS category depending upon the Ultrasonographic-Mammographic and MRI findings. Statistical analysis of BI-RADS 3 and 4 masses were performed by Fischer’s exact test and Pearson chi square test. Results; For the evaluation of BI-RADS 3 mass lesions, pre and post-contrast spectroscopy had about 100% sensitivity and specificity. According to the BI-RADS 4 lesions; H-MRS before and after contrast admistration, presented 81-73 % sensitivity with 100 % specificity for both acquisitons. Pre and post-contrast H-MRS, had 91-85% sensitivity and 56-44% specificity for all BIRADS-3 and 4 lesions of 55 patients. Pre-contrast MR-Spectroscopy had significant statistical differences with regard to histopathology for all BI-RADS 3 and 4 lesions (p<0.05), however post-contrast spectroscopy did not have any statistical differences from the biopsy (p>0.05). Conclusion; H-MRS, especially the one performed before the contrast application, was useful for characterizing the BI-RADS 3 and 4 breast lesions, further improve the sensitivity and specificity of breast MR imaging and influence patient treatment options.